RARE-20. A RARE CASE OF A PRIMARY CENTRAL NERVOUS SYSTEM NEUROENDOCRINE CARCINOMA AND SUCCESSFULL THERAPY IN A FIVE-YEAR-OLD CHILD. (1st June 2021) - Stepien, Natalia; Haberler, Christine; Schmook, Maria-Theresa; Gojo, Johannes; Azizi, Amedeo A; Czech, Thomas; Slavc, Irene; Peyrl, Andreas
Abstract: Neuroendocrine tumors (NETs) are rare neoplasms predominantly arising in the GI-tract or the lungs of adults. To date, only ten cases of primary CNS NETs have been reported with just three of them describing a neuroendocrine carcinoma (NEC) in patients aged 34–77 years and none occurring in a child. We report on a previously healthy 5-year-old boy, who presented with headaches, nausea and vomiting and was diagnosed with a left cerebellar solid mass with a cystic component, radiologically suggestive of a pilocytic astrocytoma. After gross-total resection, histological analysis revealed an epithelial tumor growing in a nest-like pattern with a very high mitotic frequency, staining positive for CK8, CK18 and CK19. Chromogranin A and synaptophysin expression indicated a neuroendocrine differentiation. Molecular analysis of the tumor tissue revealed a KRAS- splice-site mutation (c451-3C>T). After extensive search for an extracranial primary, including Ga-68 DOTANOC-PET-CT, the diagnosis of a primary CNS NEC was made, and proton irradiation was performed. However, the patient developed an in-field recurrence just five weeks after the end of radiotherapy. The tumor was re-resected en-bloc, showing vital tumor tissue, demonstrating its aggressiveness. Chemotherapy consisting of etoposide, cisplatin and ifosfamide was initiated. After two cycles chemotherapy was continued with etoposide and carboplatin for another four cycles. The patient remains disease free one year after the end of relapse-treatment, supporting the beneficial effect of platinum- and etoposide-based chemotherapy for this tumor entity. Physical exam revealed a sagittal synostosis with a mild dolichocephaly. Interestingly, the KRAS-mutation was discovered to be a maternal germline mutation, previously described as likely benign. However, alterations of the RAS/MAPK pathway have been described in NECs and in craniosynostosis cases. It remains to be elucidated whether the KRAS-mutation is merely a variant of uncertain significance or might have been implicated in the development of this exceptional tumor.